THE COMPARISON OF MSMEs FINANCING PROPORTION IN COMMERCIAL BANKING AND SHARIA BANKING IN INDONESIA - Nusrotul Hidayah; Eko Fajar Cahyono (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to compare the proportion of MSME financing from total financing in commercial banking and Islamic banking in Indonesia in 2014- 2018. The approach used in this study is a quantitative approach with the Mann Whitney test. This study used secondary data obtained from the Financial Services Authority’s (OJK) website. The study result showed a significance value (probability) that was smaller than 0.05, meaning that the proportion of MSME financing to total financing in Islamic banking in Indonesia was greater than the proportion of MSME credit to total credit. It shows that the presence of Islamic banking has had a positive impact on the growth of the real sector, especially MSME through mudharabah and musharakah schemes or direct investment schemes and profit sharing so that MSME can contribute to employment, domestic income, and resilience in dealing with economic shocks.Keywords: Banking, Credit, Financing, MSME